Disparity in Judicial Decisions in Narcotics Crimes (A Study of Verdict No. 1192/Pid.Sus/2024/PN.Mdn and Verdict No. 1035/Pid.Sus/2024/PN.Mdn) - Fithri, Beby Suryani (Universitas Medan Area, 2024)
This research aims to analyze inequality in judges' decisions in drug crime cases by studying two court decisions, namely Decision No. 1192/Pid.Sus/2024/PN.Mdn and Decision No. 1035/Pid.Sus/2024/PN.Mdn. These two decisions involved defendants who were subject to the same sentence despite significant differences in their roles and the amount of evidence found. M. Ramadhan acted as an intermediary with evidence of 0.79 grams of narcotics, while Ari Wibowo was more active in the narcotics network despite only having evidence of 0.04 grams. This research uses a qualitative method with a case study approach to evaluate the factors that influence judges' decisions, such as the role of the defendant and the amount of evidence in sentencing. The results showed that despite differences in the roles and evidence involved, both defendants were sentenced to the same sentence, namely 7 years and 6 months' imprisonment and a fine of Rp 1,000,000,000, with a subsidiary of 1 year's imprisonment. This finding indicates an inconsistency in the sentencing considerations, and suggests the need for stricter standardization in sentencing in drug cases to achieve justice that is more in line with the conditions and facts of each case.